SISTEM MUḌĀRABAH DAN APLIKASINYA PADA BANK SYARIAH MANDIRI CABANG PALU - Murniati Ruslan (State Institute of Islamic Studies (IAIN) Palu, 2013)
Abstract: Bank Syariah Mandiri is a state bank who first introduced a system of sharia. In a way, this bank was applying one system of cooperation with customers called muḍārabah. The systems of muḍārabah are also applicated in the Bank Syariah Mandiri Branch Palu, which was established in 2003. This study discusses the theory and application of muḍārabah system in Bank Syariah Mandiri Branch Palu. The results showed that the application of muḍārabah system in Bank Syariah Mandiri Branch Palu has not been fully realized purely in accordance with the theoretical foundation of muḍārabah system suggested by experts, despite the commitment of Bank Syariah Mandiri Branch Palu to customers has increased significantly.Kata Kunci: aplikasi, sistem muḍārabah, Bank Syarih Mandiri.